Boundary Integral Formulation of Frictionless Contact Problems Based on an Energetic Approach and Its Numerical Implementation by the Collocation BEM - Panagiotopoulos, Christos G.; Mantič, Vladislav; García, Israel G.; Graciani, Enrique (Frontiers in Built Environment, 2018)
A unified methodology to solve problems of frictionless unilateral contact as well as adhesive contact between linear elastic solids is presented. This methodology is based on energetic principles and is casted to a minimization problem of the total potential energy. Appropriate boundary integral forms of the energy are defined and the quadratic problem form of the contact problem is proposed. The problem is solved by the collocation boundary element method (BEM). To solve the quadratic problem two algorithms are developed, both being variants of the well-known conjugate gradient algorithm. The difference between them is given by an explicit construction or not of the quadratic-problem matrix. This matrix has the same physical meaning as the stiffness matrix commonly used in the context of the finite element method (FEM). Both symmetric and non-symmetric formulations of this matrix are presented and discussed, showing that the non-symmetric one provides more accurate results. The present procedure, in addition to its interest by itself, can also be extended to problems where dissipative phenomena take place such as friction, damage and plasticity. Elements of the numerical implementation are briefly presented and the numerical solution of some standard problems of frictionless contact are given and compared to those obtained by other well-known BEM and FEM procedures for contact problems.